CÁC TRITERPEN TỪ THÂN CÂY BA SOI HỌ THẦU DẦU (EUPHORBIACEAE) - Thoa, Hà Thị; Hương, Đoàn Thị Mai; Cường, Phạm Văn; Litaudon, Marc; Hùng, Nguyễn Văn; Minh, Châu Văn (Vietnam Journal of Science and Technology, 2012)
TRITERPENOIDS FROM THE STEMS OF MACARANGA DENTICULATE (EUPHORBIACEAE) In Vietnam, the genus Macaranga consists of 15 species, some of these species were widely used as traditional medicines to treat diseases tussive, pyretic, inflame, infection. The plant Macaranga denticulate was selected for chemical study because of its cytotoxic. From the stems of this plant, four triterpenoids 3-acetylaleuritolic (1), epitaraxerol (2), taraxerone (3),  maslinic acid (4) were isolated. Their structures were elucidated by using IR, MS and NMR spectroscopic methods.